Increasing Pediatric Hearing Aid Use: Considerations for Clinical Practice. - Muñoz, Karen; Markle, Kali; San Miguel, Guadalupe G.; Twohig, Michael P. (American Journal of Audiology, 2023)
Purpose: Hearing aid use can be variable for young children, and inconsistent wear time can undermine spoken language development. This study explored the effectiveness of hearing aid data logging (DL) awareness and coaching sessions on increasing hours of hearing aid use. We also collected qualitative data on challenges participants experienced managing hearing aid use. Method: We used a single-subject design that included three conditions, during a 6-week period, in the same order for each participant. Condition A was baseline, Condition B was DL monitoring alone, and Condition C was remote coaching calls plus DL monitoring. Results: Hours of hearing aid use increased for each child from baseline to the end of the study, ranging from 1.19 to 4.4 hr. Mothers reported that the coaching calls were beneficial and helped them identify and problem-solve issues. Conclusions: Parents were able to increase hours of hearing aid use with DL awareness and coaching support. Tele-audiology offers an opportunity to provide parents with more frequent support that can be individualized based on their situation, challenges, and family needs.